The effect of increasing thread depth on the initial stability of dental implants: an in vitro study - Cucinelli, Chiara (2024)
Background: The long-term success of dental implants largely depends on achieving primary stability, previously described as crucial to obtaining osseointegration and immediate loading protocol requirements. Implant thread depths seem to be one of the key factors influencing primary stability, particularly in low-density bone. Insertion torque (IT) and resonance frequency analysis (RFA) are considered the most reliable tests to assess primary stability. The aim of this work was to evaluate how different thread depths of commercially available dental implants affect primary stability in low-density D3 bone. Materials and Methods: An in vitro study was carried out between February 2024 and March 2024. Twenty-four dental implants were divided into four groups (six implants each) according to their thread depths (Group A: 4 mm, Group B: 4.5 mm, Group C: 5 mm, Group D: 5.5 mm) and were inserted in D3-type artificial bone blocks. The main outcome variables were the IT and the Implant Stability Quotient (ISQ) measured in four different areas of the implant (buccal, lingual, mesial, and distal) with an Osstel® ISQ reader. Descriptive and inferential analyses of the data were performed, and the significance value was set at 5%. Results: A total of 24 implants were analyzed. The highest IT values were obtained in Group D, with a mean of 54.03 Ncm (standard deviation (SD) = 8.99), while the lowest measurements were observed in Group A (mean = 25.12; SD: 2.96 N.cm). The mean ISQ values were consistently higher in Group D for each analyzed area, with a mean of 70.13 N.cm (SD = 1.12). Conclusions: Taking into consideration the limitations of this in vitro study, greater thread depths seem to increase the primary stability of dental implants placed in soft bone. Furthermore, a positive correlation was observed between all IT and ISQ values, regardless of the thread depth.